Biosorption of Lanthanides from Aqueous Solutions Using Pretreated Buccinum tenuissimum Shell Biomass - Yusuke Koto; Naoki Kano; Yudan Wang; Nobuo Sakamoto; Hiroshi Imaizumi (Bioinorganic Chemistry and Applications)
Biosorption experiment from aqueous solutions containing known amount of rare earth elements (REEs) using pre-treated Buccinum tenuissimum shell was explored to evaluate the efficiency of shell biomass as sorbent for REEs. In this work, four kinds of sieved shell samples: (a) “Ground original sample”, (b) “Heat-treatment (480∘C, 6 hours) sample”, (c) “Heat-treatment (950∘C, 6 hours) sample” and (d) “Heat-treatment (950∘C, 6 hours) and water added sample” were used. Furthermore, to confirm the characteristics of the shell biomass, the crystal structure, the surface morphology, and the specific surface area of these shell samples were determined. Consequently, the following matters have been mainly clarified. (1) The crystal structure of the shell biomass was transformed from aragonite (CaCO3) into calcite (CaCO3) phase by heat-treatment (480∘C, 6 hours); then mainly transformed into calcium oxide (CaO) by heat-treatment (950∘C, 6 hours), and calcium hydroxide (Ca(OH)2) by heat-treatment (950∘C, 6 hours) and adding water. (2) The shell biomass showed excellent sorption capacity for lanthanides. (3) Adsorption isotherms using the shell biomass can be described by Langmuir and Freundlich isotherms satisfactorily for lanthanides except “heat-treatment (950∘C, 6 hours) sample”. (4) Shell biomass (usually treated as waste material) can be an efficient sorbent for lanthanides in future.